1982
DOI: 10.1042/bj2020677
|View full text |Cite
|
Sign up to set email alerts
|

Immuno-electron-microscopic studies on the subcellular distribution of rat liver epoxide hydrolase and the effect of phenobarbitone and 2-acetamidofluorene treatment

Abstract: The distribution of rat liver epoxide hydrolase in various subcellular fractions was investigated by immuno-electron-microscopy. Ferritin-linked monospecific anti-(epoxide hydrolase) immunoglobulins bound specifically to the cytoplasmic surfaces of total microsomal preparations and smooth and rough microsomal fractions as well as the nuclear envelope. Specific binding was not observed when the ferritin conjugates were incubated with peroxisomes, lysosomes and mitochondria. The average specific ferritin load of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
2

Year Published

1982
1982
1997
1997

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
1
4
2
Order By: Relevance
“…This value would indicate that these proteins have an Neyt/Cexo orientation in the membrane of the ER. Experimental data indicate that the rat mEH has an Nexo/Ceyt orientation in the membrane [10,11]; however, these findings are at variance with a recent report on the membrane topology of mEH [12].…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This value would indicate that these proteins have an Neyt/Cexo orientation in the membrane of the ER. Experimental data indicate that the rat mEH has an Nexo/Ceyt orientation in the membrane [10,11]; however, these findings are at variance with a recent report on the membrane topology of mEH [12].…”
Section: Discussioncontrasting
confidence: 75%
“…A co-translational insertion into the ER was also shown for mEH, and the N-terminus of this protein is not proteolytically processed during its insertion into membranes [8,9]. There is evidence that this enzyme has a similar orientation in the membrane to that of microsomal cytochromes P-450 [10,11]. However, a recent report [12] demonstrated that mEH was identical with a bile acid transport protein which could assume two opposite orientations within the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore decided to invert the membrane topology of mEH as an important step in the evaluation of the resulting toxicological consequences. In the course of these studies we have firmly established the mEH membrane topology, which until now has been disputed [13,14,17].…”
Section: Discussionmentioning
confidence: 99%
“…These values suggest that mEH from these species have exclusively a type II orientation in the membrane of the ER [11]. However, on the basis of labelling experiments with membrane-impermeant protein-reactive fluorescent probes, and on immuno-electron microscopy, there is evidence that the mEHlike cytochrome P-450 has a type I membrane orientation [13,14]. If this is correct, the sequence of events catalysed by cytochrome P-450 and by mEH, leading to the formation of the ultimate carcinogenic metabolites of polycyclic aromatic hydrocarbons, would take place exclusively at the cytosolic face of the ER, allowing highly efficent metabolic channelling [15].…”
Section: Introductionmentioning
confidence: 99%
“…The microsomal epoxide hydrolase which has been studied in detail [reviews 3,4] has been purified from rat, rabbit and human livers [5 -71. This enzyme has immunological properties very similar to those of the epoxide hydrolase found in nuclear membranes [8,9]. On the other hand, the cytoplasmic hydrolase appears to differ markedly from the microsomal hydrolase, and the two enzymes are immunologically distinguishable [lo].…”
mentioning
confidence: 89%